ANALISIS BIBLIOMETRIK PERKEMBANGAN MUTAKHIR DALAM STUDI ANISOTROPI SEISMIK (2017 -2022): BIBLIOMETRIC ANALYSIS OF RECENT DEVELOPMENT IN THE SEISMIC ANISOTROPY STUDIES (2017 -2022) - Yuda, Himmes Fitra; Ronoatmojo, Imam Setaiji; Burhannudinnur, Muhammad; Nuryana, Suherman Dwi (Journal of Geoscience Engineering and Energy, 2024)
The development of seismic anisotropy needs to be studied systematically hence research could be focused on the latest scientific knowledge, therefore a bibliometric analysis is needed as a measurement of citation strength in the form of mapping "co-occurrence", "co-author" and "co- citation", thus the strength of the research direction could be well understood. The software which is used; VOSviewer version 1.6.18 examined at least 494 papers in the SCOPUS domain during 2017 -2020. It appears from the results that the development of the seismic anisotropy are very rapidly dominated by the needs of the applied science and pure science. The heavily publication countries are United States of America, China and Japan. However, in reality, this density does not necessarily correspond to the number of citations between countries, as well with publications in Japan.